Pengaruh pembangunan infrastruktur jalan, distribusi pendapatan, dan zis (zakat, infaq, sedekah) terhadap pertumbuhan ekonomi - Ghozali, Muhamad (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2022)
Abstract: The research approach used is quantitative, The data source in this study is secondary data obtained through the results of reports published by the Central Statistics Agency (BPS), the National Amil Zakat Agency (BAZNAS) and trusted websites. Sampling included in non-probability sampling is purposive sampling where the data criteria studied are complete data from 2011 to 2020. Then the data is processed using the eviews 9 application. Based on the data analysis that has been carried out on all the data obtained has the following results; positive and insignificant influence between Road Infrastructure Development and Economic Growth, there is an insignificant negative influence between vaiabel Income Distribution on Economic Growth, there is a positive and significant influence between the ZIS variables on Economic Growth, and simultaneously all three independent variables have a positive and significant influence on Economic Growth.